Organizational Performance Achievements at The Tanjungpinang City District Office - Risnawati; Satriadi; Selvi Fauzar; Hasnarika; Rapida Nuriana (Jurnal Ekonomi dan Bisnis Digital, 2022)
The Tanjungpinang Kota District Office is a public organization located in the Tanjungpinang City area. Tanjungpinang Kota sub-district has the task of carrying out the wheels of government and public services at the sub-district level. The achievement of these goals is certainly influenced by the performance of the organization as a whole. As a sub-district located in the City, this is certainly a representation of other sub-districts that researchers are interested in discussing. This study aims to analyze how the performance of the Tanjungpinang City District organization in achieving goals according to the vision and mission. To see the performance of Tanjungpinang City, the researchers looked at various aspects, namely, productivity, responsiveness, service quality, cooperation, resource use and timeliness. The second objective is to describe the factors inhibiting organizational performance in Tanjungpinang Kota District. This research is a qualitative descriptive study with reference to the concept of performance indicators coupled with the existing conditions at the research locus. Based on the results of the study, it can be explained that the organization's performance has been going well, such as the indicators of productivity, responsiveness, service quality, cooperation and timeliness. The indicators that still have obstacles are human resources and infrastructure.